2020
DOI: 10.3389/fmolb.2020.00140
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis PcrA Couples DNA Replication, Transcription, Recombination and Segregation

Abstract: Bacillus subtilis PcrA abrogates replication-transcription conflicts in vivo and disrupts RecA nucleoprotein filaments in vitro. Inactivation of pcrA is lethal. We show that PcrA depletion lethality is suppressed by recJ (involved in end resection), recA (the recombinase), or mfd (transcription-coupled repair) inactivation, but not by inactivating end resection (addAB or recQ), positive and negative RecA modulators (rarA or recX and recU), or genes involved in the reactivation of a stalled RNA polymerase (recD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 97 publications
(214 reference statements)
2
34
2
Order By: Relevance
“…PcrA is a UvrD-like DNA helicase that shares a significant degree of structural similarity with E. coli UvrD (UvrD Eco ), Rep Eco and with Saccharomyces cerevisiae Srs2 enzyme [ 15 ]. PcrA is considered to be an essential enzyme because its deletion or an inactive variant ( pcrA K37A), whose product lacks ATPase and helicase activities, renders non-viable cells [ 16 , 17 ]. PcrA depletion lethality, however, is suppressed by the recO16 (formerly termed recL16 ) mutation or by recA inactivation, but not by addAB (counterpart of recBCD Eco ) inactivation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…PcrA is a UvrD-like DNA helicase that shares a significant degree of structural similarity with E. coli UvrD (UvrD Eco ), Rep Eco and with Saccharomyces cerevisiae Srs2 enzyme [ 15 ]. PcrA is considered to be an essential enzyme because its deletion or an inactive variant ( pcrA K37A), whose product lacks ATPase and helicase activities, renders non-viable cells [ 16 , 17 ]. PcrA depletion lethality, however, is suppressed by the recO16 (formerly termed recL16 ) mutation or by recA inactivation, but not by addAB (counterpart of recBCD Eco ) inactivation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could indicate that PcrA lacking the CTD can still interact weakly with RNAP (as we have discussed above) or that the toxic effect we observe arises from another role of this multifunctional enzyme that does not require the CTD. We also tested whether removal of mfd (that has been shown to counteract PcrA essentiality (Moreno-del Alamo et al, 2020)) could relieve the mutant’s toxicity but found that the deletion had no effects on the growth defect ( Figure S10B ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent work in E. coli has shown that uvrD is synthetically lethal with rnhA , in agreement with a role for this helicase in unwinding R-loops that may be distinctive from those dealt with by other R-loop suppression factors (Wolak et al, 2020). An R-loop suppression function might also explain why loss of PcrA leads to hyper-recombination and the formation of RecFOR- and RecA-dependent toxic recombination intermediates (Arthur and Lloyd, 1980; Moreno-del Alamo et al, 2020; Petit and Ehrlich, 2002; Veaute et al, 2005). The displaced ssDNA within an R-loop may act as a “frustrated” substrate for ssDNA gap repair, resulting in RecA recruitment and strand exchange but failing to resolve correctly into repaired products because of the presence of the R-loop and TEC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, E. coli cells can perform transcriptioncoupled repair through an Mfd-independent mechanism and the activity of UvrD (Epshtein et al, 2014). This Mfd-independent transcription-coupled repair has been postulated to occur in B. subtilis (Moreno-Del Alamo et al, 2020). Also, DNA lesions of oxidative nature modulate growth and stationary-phase associated Mfd-dependent mutagenic events in this Grampositive microorganism (Leyva-Sánchez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%